LncRNA SNHG4 Regulates Lipid Metabolism and Inflammation in Non-Alcoholic Fatty Liver Disease by Targeting miR-34b-5p/XIAP Axis - Ding, YanJu; Zheng, Sheng; Fu, Xin Nian; Ma, Chi; Juan, Yang (Turkish Journal of Gastroenterology, 2025)
Background/Aims: This research aimed at probing the mechanism of long non-coding RNA small nucleolar RNA host gene 4 (SNHG4) in regulating lipid metabolism and inflammation in non-alcoholic fatty liver disease (NAFLD). Materials and Methods: L02 and THLE-2 cells were stimulated with free fatty acids (FFA) and transfected. Lipid accumulation was detected through Oil Red O staining, measurements of triglyceride and total cholesterol were taken, and the levels of tumor necrosis factor-α, interleukin (IL)-1β, and IL-6 were assessed using enzyme-linked immunosorbent assays. The assessment of gene expression was conducted using real-time reverse transcriptase-polymerase chain reaction and Western blot techniques. The interplay between SNHG4 and miR-34b-5p/X-linked inhibitor of apoptosis protein (XIAP) was evaluated. Results: Free fatty acids downregulated SNHG4 and XIAP and upregulated miR-34b-5p in L02 and THLE-2 cells, leading to lipid metab olism disorder and inflammation. SNHG4 overexpression mitigated the lipid metabolism disorder and inflammation triggered by FFA, while this effect was suppressed by silencing XIAP. In contrast, SNHG4 knockdown aggravated FFA-induced lipid metabolic and inflam matory disorders, whilst this effect was rescued by inhibiting miR-34b-5p. Conclusion: SNHG4 regulates lipid metabolism and inflammatory disorders in NAFLD by targeting the miR-34b-5p/XIAP axis. Cite this article as: Ding Y, Zheng S, Fu XN, Ma C, Yang J. LncRNA SNHG4 regulates lipid metabolism and inflammation in non alcoholic fatty liver disease by targeting miR-34b-5p/XIAP axis. Turk J Gastroenterol. 2025;36(10):629-640.